Weekly hours of informal caregiving and paid work, and the risk of cardiovascular disease. (22nd December 2017) - Mortensen, Jesper; Dich, Nadya; Lange, Theis; Ramlau-Hansen, Cecilia Høst; Head, Jenny; Kivimäki, Mika; Leineweber, Constanze; Hulvej Rod, Naja
Abstract: Background: Little is known on the association between weekly hours of informal caregiving and risk of cardiovascular disease (CVD). The objective was to investigate the individual and joint effects of weekly hours of informal caregiving and paid work on the risk of CVD. Methods: Pooled analysis with 1396 informal caregivers in gainful employment, from the Swedish Longitudinal Occupational Survey of Health and the Whitehall II study. Informal caregiving was defined as care for an aged or disabled relative. The outcome was CVD during 10 years follow-up. Analyzes were adjusted for age, sex, children, marital status and occupational grade. Results: There were 59 cases of CVD. Providing care >20 h weekly were associated with a higher risk of CVD compared to those providing care 1–8 h weekly (hazard ratio = 2.63, 95%CI: 1.20; 5.76), irrespectively of weekly work hours. In sensitivity analyzes, we found this risk to be markedly higher among long-term caregivers (6.17, 95%CI: 1.73; 22.1) compared to short-term caregivers (0.89, 95%CI: 0.10; 8.08). Caregivers working ≥55 h weekly were at higher risk of CVD (2.23, 95%CI: 1.14; 4.35) compared to those working 35–40 h weekly. Those providing care >8 h and working ≤40 h weekly had a higher risk of CVD compared to those providing care 1–8 h and working ≤40 h (3.23, 95%CI: 1.25; 8.37). Conclusion: A high number of weekly hours of informal caregiving as opposed to few weekly hours is associated with a higher risk of CVD, irrespectively of weekly work hours. The excess risk seemed to be driven by those providing care over long periods of time.